49th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2011
DOI: 10.2514/6.2011-1228
|View full text |Cite
|
Sign up to set email alerts
|

Averaging of the Nonlinear Dynamics of Flapping Wing Micro Air Vehicles for Symmetrical Flapping

Abstract: First order equations of motion for a flapping wing micro-air vehicle are presented. The first order, longitudinal equations of motion are obtained from the second-order, strongly coupled, multi-body equations of motion using an approximate inverse. The nonlinear dynamics of the longitudinal equations of motion are averaged using two different methods: local averaging over a fully flapping cycle and local averaging over quarter-flapping cycles. Open loop simulations are presented, near a hover condition, for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Taha et al (2012) noted in their review paper that the averaging of the dynamic forcing from the flapping wings may omit important aspects, such as the possible energy transfer from the highfrequency modes to the low-frequency modes of the body motions. Further, Orlowski and Girard (2011b) showed that the wingbeat-cycle-averaging of the flapping wing aerodynamics resulted in a flight trajectory different from the numerical solution of the full equations. For the numerical flight simulations in this study, we performed a direct time integration of the fully coupled 6-DOF nonlinear multibody dynamics equations of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Taha et al (2012) noted in their review paper that the averaging of the dynamic forcing from the flapping wings may omit important aspects, such as the possible energy transfer from the highfrequency modes to the low-frequency modes of the body motions. Further, Orlowski and Girard (2011b) showed that the wingbeat-cycle-averaging of the flapping wing aerodynamics resulted in a flight trajectory different from the numerical solution of the full equations. For the numerical flight simulations in this study, we performed a direct time integration of the fully coupled 6-DOF nonlinear multibody dynamics equations of motion.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used by Dietl and Garcia (2008) Averaging theory, on the other hand, predicts the behavior of the original time varying system 'on an average'. Averaging technique is the more popular choice for analyzing the system as opted by Oppenheimer et al (2011), Deng et al (2006a, Khan and Agrawal (2007), Orlowski and Girard (2011a), Karásek and Preumont (2012). Averaging for flapping wing MAVs have been dealt with rigorously in Deng et al (2006a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this thesis we have discussed averaging method, as applied to the MAV system. Since the idea of averaging is to get a time invariant model for control purposes, it is unsure how quarter cycle averaging proposed in Orlowski and Girard (2011a) is useful for purpose of control.…”
Section: Introductionmentioning
confidence: 99%
“…While flapping-wing dynamics are highly complex, warranting investigation into multi-body modelling, 37,11,38,39 several studies have demonstrated that for basic considerations, e.g. in the context of design and control work, the conventional fixed-wing aircraft equations of motion represent a suitable description for many insects and FWMAVs.…”
Section: Iiia Local Model Estimationmentioning
confidence: 99%
“…Particularly low-order models of flapping-wing dynamics and aerodynamics typically have a limited applicability range and/or have not been validated in different conditions with free-flight data. 7,8,9,10,11,12,13,14 However, it is essential to know how a system behaves in all its operating conditions, in order to ensure an effective operation and maximise its performance. Furthermore, accurate global models are highly valuable and often indispensable to provide more realistic and comprehensive simulation possibilities, support the development and testing of new controllers and allow for the application of more advanced control approaches.…”
Section: Introductionmentioning
confidence: 99%